2011
DOI: 10.1007/s12229-011-9088-6
|View full text |Cite
|
Sign up to set email alerts
|

Palm Management in South America

Abstract: We reviewed information on management of useful palms in South America. We documented management for 96 species, from incidental activities intended to increase populations of wild palms to the inclusion of palms in complex agroforestry systems. Two species, Bactris gasipaes and Parajubaea cocoides, are domesticated. Managed species are remarkably fewer than species used in the region, which suggests that harvesters often disregard the fate of the species they use. The best way of managing palms is to employ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 80 publications
(53 reference statements)
1
83
0
10
Order By: Relevance
“…This review paper highlights scientific knowledge about peach palm fruit production that comes from different technical disciplines and has not been covered in previous reviews-at least not from such a broad perspective (e.g., Mora-Urpí et al 1997;Clement et al 2004Clement et al , 2010Bernal et al 2011). The review also identifies aspects that research has so far neglected but have potential to improve the well-being of people involved in peach palm production and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…This review paper highlights scientific knowledge about peach palm fruit production that comes from different technical disciplines and has not been covered in previous reviews-at least not from such a broad perspective (e.g., Mora-Urpí et al 1997;Clement et al 2004Clement et al , 2010Bernal et al 2011). The review also identifies aspects that research has so far neglected but have potential to improve the well-being of people involved in peach palm production and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…At the end we will make a number of recommendations, which elaborate on the findings of a recently completed EU 7th Framework project (EU-PALMS 2009-2013) on sustainable harvesting of palms in tropical South America (results published in [5,[10][11][12]). Table 1 summarizes some of the most important features that characterize palms (family Arecaceae) as a plant group and how these affect their agricultural potential.…”
Section: Study Region and Methodological Approachesmentioning
confidence: 99%
“…Hence there is very little attention on their potential in home-gardens and agroforestry cultivation systems. Many palm species are underexploited and the products they deliver are often extracted in a way that is both inefficient and unsustainable [12]. Detailed studies conducted in north-western South America have shown that resource depletion due to lack of proper management has led to rising prices on local and regional markets [11].…”
Section: Introductionmentioning
confidence: 99%
“…Astrocaryum chambira (chambira or cumare) is one of the most important palm species for the indigenous communities of the northwestern Amazon as the fibers obtained from its unexpanded leaves are used to make a great variety of products for daily needs, such as hammocks, bags, or fishing nets (Jensen & Balslev 1995;Vormisto 2002;Coomes 2004;Bernal et al 2011;Mesa & Galeano 2013). Its harvest and processing are a part of aboriginal traditions, and these activities represent important times for social interactions (Gallego 2005).…”
Section: Introductionmentioning
confidence: 99%